Organisational culture for information managers - Oliver, Gillian (Chandos information professional series., 2011)
"In today's digital environment the workplace is characterised by individuals creating information perhaps independently of formal systems, or establishing new systems without knowledge of information management requirements. This book explains and explores the concept of organisational culture, specifically within the domain of information management. It draws on the author's wide-ranging practical experience in different workplaces and uses research findings from cross-cultural studies of information management."--Publisher's website